Climate change impacts on sea level rise to flood depth and extent of Sarawak River - Kuok, King Kuok; Mersal, Mohd. Elfy; Chiu, Po Chan; Chin, Mei Yun; Rahman, Md. Rezaur; Bakri, Muhammad Khusairy Bin (Frontiers in Water, 2022)
Abstract — This study focuses on the impact of climate change on Sarawak river flow due to heavy rainfall and the backflow of sea level. The sea level around Sarawak is expected to rise at 3.6 mm/year. When surface runoff meets seawater backflow, especially during king tides, determining the flood inundation level at low-lying regions along the Sarawak River is critical to prepare appropriate mitigation measures. The hydrodynamic model was developed using Infoworks River Simulation (RS) software. The flow of the Sarawak River is modeled from Git Station to Muara Tebas port. Various data are input into the hydrodynamic model for calibration and validation, including boundary conditions, river networks, ground models, river cross-section, water level, and rainfall data. The simulation was carried out for the years 2050 and 2080. The flood maps were generated to depict flood depth, extent, and submerged areas. In 2020, the backflow of seawater did not overwhelm Kuching City, which is located within the Sarawak River Basin.- However, many low-lying locations along Sarawak River are expected to be inundated by 2050, with the flood depth ranging from 1 m to 4 m. In 2080, the average increment of flood depth is predicted to be 1 m especially for low-lying areas compared to year 2050. Hence, the relevant authorities must take proactive efforts to manage the growing flood challenges caused by climate change, particularly in low-lying areas.